One‐Shot Measurement of Effectiveness Factors of Chemical Conversion in Porous Catalysts. Issue 24 (27th December 2018) - Chmelik, Christian; Liebau, Michael; Al‐Naji, Majd; Möllmer, Jens; Enke, Dirk; Gläser, Roger; Kärger, Jörg
Abstract: The front cover artwork for issue 24/2018 is provided by scientists at the Universität Leipzig, Max Planck Institute of Colloids and Interfaces, and Institute for Non‐Classical Chemistry e. V. (Germany). The image illustrates the use of IR microimaging for monitoring the mean concentration of both reactant and product molecules within a catalyst particle during a chemical reaction, allowing the one‐shot determination of its effectiveness factor. The front cover idea and design by Alaa Al‐Naji is greatly acknowledged. See the Full Paper itself athttps://doi.org/10.1002/cctc.201801530 . Abstract : "On‐line IR microimaging allows the determination of the effectiveness factor of a chemical reaction within a porous catalyst by a single "one‐shot" measurement." This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttps://doi.org/10.1002/cctc.201801530 .